El sentido del modelo de formación de la Facultad de Ciencias de la Educación de la UNIFE - Escalante Rivera, Mónica (2012)
Education School training model sense is only appreciated when its operationis observed in a scheme of interrelated actions. The sense presents a relationalcondition and is defined by time and circumstances; therefore, it can observechanges. The sense is dynamic.In order to describe and chart the direction of the training model was necessaryto take distance from the forming action that has been developed over the yearsand analyzed the context in which it takes place.Give response to the demands of reality has always been a School concern, since itis what gives meaning to the training model. Reflect on the model meaning allowedsizing characteristics of the training reality, involved to make a constant assessmentof the activities related to pedagogical and disciplinary perspective that were beingdeveloped. In addition, measure its social function in terms of management andprofessional training, as well as promote the transformation, research, creation andcommitment to become agents of change.